Analysis of clinical features and genetic variants in Chinese children with pyridoxine-dependent epilepsy: a case series study - Yu, Xixi; Zhang, Xin; Qiu, Shiyan; Yang, Li; Li, Xin; Shi, Dongyu (Frontiers in Neurology, 2025)
ObjectiveTo summarize the clinical features and the spectrum of ALDH7A1 gene variants in Chinese children with pyridoxine-dependent epilepsy (PDE).MethodsClinical data were collected from six pediatric patients with PDE treated at Linyi People’s Hospital (2017–2023). Whole-exome sequencing, in conjunction with Sanger sequencing, was used to screen for ALDH7A1 gene variant sites. Bioinformatics methods were applied in combination with clinical phenotype assessment to evaluate the pathogenicity of the variants.ResultsIn six cases of PDE, the male-to-female ratio was 2:4. Five cases began in the neonatal period, and one in early infancy. Three cases experienced hypoxiaetal distress or respiratory distress. Two cases had a family history of recurrent miscarriages or premature deaths of siblings due to seizures. Seizure types varied among the cases. Three individuals experienced cluster seizures, two were heat-sensitive, and four suffered from status epilepticus. Video EEGs of four children revealed hypsarrhythmia, focal, or multifocal discharges initially, which normalized within 3 days to 8 months following vitamin B6 treatment. All patients initiated regular vitamin B6 therapy between 32 days and 17 months post-onset, with an initial dose ranging from 7.7 to 12.5 mg/(kg·d). During follow-up until the age of 1 to 8 years, the maintenance dose was adjusted to 3.3–7.8 mg/(kg·d). Two patients who began standardized treatment before the age of 3 months experienced normal development. The remaining patients showed mild to moderate developmental delays. Eight variants were identified, including a hotspot in Chinese children: c.1008+1G>A, and two recurrent sites: c.1061A>G and c.1547A>G. Additionally, three variants were novel.ConclusionPyridoxine-dependent epilepsy must be distinguished from hypoxic–ischemic encephalopathy and other thermally sensitive epilepsies. The severity of the condition and neurodevelopmental outcomes in affected children vary significantly. Early administration of low-dose pyridoxine can effectively control seizures and reverse EEG abnormalities, potentially improving long-term neurodevelopmental outcomes. c.1061A>G and c.1547A>G may be hotspot variants in Chinese children with PDE.